2018
DOI: 10.1016/j.gaitpost.2018.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Functional behaviour of spinal muscles after training with an exercise device developed to recruit and train postural muscles

Abstract: This study investigated the effects of a single exercise session using a device developed for postural muscle training on the function of postural muscles in healthy, pain free individuals. During standardised rapid arm movements, timing of onset of electromyography (EMG) was measured using intramuscular and surface recordings of the transversus abdominis (TrA), obliquus internus abdominis (OI), obliquus externus abdominis (OE), lumbar multifidus (LM) and lumbar erector spinae (LES) muscles. A single exercise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In healthy individuals, TrA activity is usually triggered before any postural disturbance, to protect the lumbar region from imposed forces. [8]. If this perturbation is not anticipated, balance disruption may occur [9].…”
Section: Introductionmentioning
confidence: 99%
“…In healthy individuals, TrA activity is usually triggered before any postural disturbance, to protect the lumbar region from imposed forces. [8]. If this perturbation is not anticipated, balance disruption may occur [9].…”
Section: Introductionmentioning
confidence: 99%
“…Holding a weight likely produces a tonic activation of the trunk muscles, which may affect the detection of trunk muscle onsets. A previous study showed that tonic activation delayed the onsets of trunk muscles during RAMT (70). A higher background muscle activity before the RAMT is likely to increase the level of descending drive, rendering 'additional' muscle activity unnecessary until later (70).…”
Section: Rapid Arm Movement Task 421 Activation Of Trunk Muscles In Apas Is Delayed After 60-day Hdt Bed Restmentioning
confidence: 92%
“…This algorithm uses statistically optimal decisions to detect changes in EMG amplitude. The automatically detected times of change in amplitude were then visually inspected to avoid spurious "onset candidates" not related to the arm movement, e.g., ECG bursts or other movement artefacts (70). Both visual determination and approximated generalized likelihood ratio method of EMG onset has been found to be highly repeatable between days during RAMT using a combination of sEMG and iEMG (25,64).…”
Section: Rapid Arm Movement: Task and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were instructed to stand with their knees slightly bent with a relaxed upper body posture while keeping the lower limbs moving in a slow, controlled manner with minimal variability in their movement speed throughout the cycle ( Weber et al, 2018 ). Visual feedback of the rotational frequency of the footplates was provided on a screen in front of the participant, who was asked to maintain a frequency of 0.42 revolutions per second with as constant a rotational frequency as possible throughout each complete rotation ( Weber et al, 2018 ). The FRED training time was increased incrementally for the first 5 days from 6 to up to 25 min of training, in 3–5 min intervals.…”
Section: Methodsmentioning
confidence: 99%